Manual Segmentation of 12 Layers of the Retina and Choroid through SD-OCT in Intermediate AMD: Repeatability and Reproducibility - Pedro Camacho; Marco Dutra-Medeiros; Luís Salgueiro; Sílvia Sadio; Paulo C. Rosa (Journal of Ophthalmic & Vision Research)
Abstract Purpose: To evaluate the repeatability and reproducibility of the segmentation of 12 layers of the retina and the choroid, performed manually by SD-OCT, along the horizontal meridian at three different temporal moments, and to evaluate its concordance with the same measurements performed by two other operators in intermediate AMD. Methods: A cross-sectional study of 40 eyes from 40 subjects with intermediate AMD was conducted. The segmentation was performed manually, using SD-OCT. The 169 measurements per eye were repeated at three time points to study the intra-operator variability. The same process was repeated a single time by two different trained operators for the inter-operator variability. Results: Forty participants (28 women and 12 men) were enrolled in this study, with an average age of 76.4 ± 8.2 (range, 55–92 years). Overall, the maximum values of the various structures were found in the 3 mm of the macula. Intra-operator variability: the highest ICC values turned out to be discovered in thicker locations. Inter-operator variability: except correlation values of 0.826 (0.727; 0.898) obtained in the OPL (T2.5) and 0.634 (0.469; 0.771) obtained in the IPL (N2), all other correlation values were > 0.92, in most cases approaching higher values like 0.98. Conclusion: The measurements of several layers of the retina and the choroid achieved at 13 locations presented a good repeatability and reproducibility. Manual quantification is still an alternative for the weaknesses of automatic segmentation. Locations of greatest concordance should be those used for the clinical control and monitoring.